2016
DOI: 10.1007/s13277-016-5013-2
|View full text |Cite
|
Sign up to set email alerts
|

Naringenin inhibits proliferation, migration, and invasion as well as induces apoptosis of gastric cancer SGC7901 cell line by downregulation of AKT pathway

Abstract: The preliminary anti-cancer activity of Naringenin (Nar) has been proven in several cancers. However, the therapeutic activity of Nar on gastric cancer SGC-7901 cell line is not yet well understood. The aim of the present study was to investigate the effect and mechanisms of Nar on proliferation, apoptosis, migration, and invasion of SGC-7901 cells. In this in vitro study, SGC-7901 cells were treated with Nar at serial concentrations. Our data showed that Nar efficiently inhibited SGC-7901 cell proliferation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(63 citation statements)
references
References 35 publications
4
59
0
Order By: Relevance
“…The mechanisms underneath this potential protective effect were investigated in studies based on gastric cancer cell lines and animal‐models. These showed anticancer effects of flavanones, a class of flavonoids contained almost exclusively in citrus fruits and juices . Hesperitin and naringenin, two of the major flavanones compounds contained in oranges and mandarins, inhibit human gastric cancer cell proliferation, migration and invasion in a dose‐ and time‐dependent manner .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanisms underneath this potential protective effect were investigated in studies based on gastric cancer cell lines and animal‐models. These showed anticancer effects of flavanones, a class of flavonoids contained almost exclusively in citrus fruits and juices . Hesperitin and naringenin, two of the major flavanones compounds contained in oranges and mandarins, inhibit human gastric cancer cell proliferation, migration and invasion in a dose‐ and time‐dependent manner .…”
Section: Discussionmentioning
confidence: 99%
“…These showed anticancer effects of flavanones, a class of flavonoids contained almost exclusively in citrus fruits and juices. [34][35][36][37][38] Hesperitin and naringenin, two of the major flavanones compounds contained in oranges and mandarins, inhibit human gastric cancer cell proliferation, migration and invasion in a dose-and time-dependent manner. 34,36 Moreover, naringenin showed a combinative effect on human gastric cell lines when administered in combination with ABT-737, an inhibitor of the antiapoptotic protein B-cell lymphoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, in SGC-7901 gastric cancer cells, naringenin treatment inhibited cancer cell proliferation, invasion, and migration and induced apoptosis, which might be related to its inhibition of the Akt signaling pathway [61]. Another study in colon cancer cells suggested that the pro-apoptotic activity of naringenin was mediated by the p38-dependent pathway [62].…”
Section: Experimental Studiesmentioning
confidence: 99%
“…Flavonoids, quercetin and rutin, protected Caco-2 cells against tert-butylhydroperoxide and menadione-induced DNA single strand breaks by their metal ion chelating ability [85]. Naringenin: Naringin is found in grapes and citrus fruit and and have shown promising results in the treatment of obesity, metabolic disorders [86] and its anti-cancer and chemo-sensitizing properties are also reported [87][88][89]. For instance, Naringenin inhibited azoxymethane induced colon carcinogenesis and lowered the number of high multiplicity aberrant foci [90].…”
Section: Dna Damage Prevention By Flavonoids With Implications To Carmentioning
confidence: 99%